Cardiopulmonary exercise testing in neuromuscular disease: a systematic review. (2nd November 2021) - Barroso de Queiroz Davoli, Gabriela; Bartels, Bart; Mattiello-Sverzut, Ana Claudia; Takken, Tim
ABSTRACT: Introduction: Cardiopulmonary exercise testing (CPET) is increasingly used to determine aerobic fitness in health and disability conditions. Patients with neuromuscular diseases (NMDs) often present with symptoms of cardiac and/or skeletal muscle dysfunction and fatigue that might impede the ability to deliver maximal cardiopulmonary effort. Although an increasing number of studies report on NMDs' physical fitness, the applicability of CPET remains largely unknown. Areas covered: This systematic review synthesized evidence about the quality and feasibility of CPET in NMDs and patient's aerobic fitness. The review followed the PRISMA guidelines (PROSPERO number CRD42020211068). Between September and October 2020 one independent reviewer searched the PubMed/MEDLINE, EMBASE, SCOPUS, and Web of Science databases. Excluding reviews and protocol description articles without baseline data, all study designs using CPET to assess adult or pediatric patients with NMDs were included. The methodological quality was assessed according to the American Thoracic Society/American College of Chest Physicians (ATS/ACCP) recommendations. Expert opinion: CPET is feasible for ambulatory patients with NMDs when their functional level and the exercise modality are taken into account. However, there is still a vast potential for standardizing and designing disease-specific CPET protocols for patients with NMDs. Moreover, future studies are urged to follow the ATS/ACCP recommendations.